Measurement of the whole body clearance of infused glycerol as a test of liver function after major hepatectomy - Tappy, Luc; Cayeux, Marie-Christine; Gillet, Michel; Koestinger, Armin; Matter, Maurice; Revelly, Jean-Pierre; Berger, Mette; Vallet, Cedric; Chioléro, René (Clinical physiology and functional imaging, 2002)
Summary Major liver resection can be used in the treatment of liver cancer. The functional capacity of liver parenchyma needs to be evaluated preoperatively because it conditions the outcome. We assessed whether the whole body clearance of glycerol, a substrate essentially metabolized in liver cells, may be suitable as a simple test of liver function. Seven patients after major hepatectomy, six patients after colectomy and 12 healthy subjects were studied. Patients were investigated on the first day after surgery. All participants were studied during a 150‐min basal period followed by a 120‐min infusion of 16 μmol kg−1 min−1 13C‐labelled glycerol. Whole body glycerol clearance was calculated from the change in plasma glycerol concentration. Whole body glucose production was measured with 6,6 2H2 glucose infused as a tracer in the basal state and during glycerol infusion. In addition, 13C glucose synthesis was monitored to quantitate gluconeogenesis from glycerol. Patients after liver resection had higher plasma glycerol concentrations and lower whole body glycerol clearance than healthy subjects and patients after colectomy. They also had higher plasma glucagon concentrations. Their fasting glucose production was mildly elevated in the fasting state and did not change after glycerol infusion, indicating a normal hepatic autoregulation of glucose production. These results indicate that whole body glycerol clearance can be simply determined from plasma glycerol concentrations during exogenous glycerol infusion. It is significantly reduced in patients after major hepatectomy, suggesting that it constitutes a sensitive test of hepatic function. Its use as a preoperative testing procedure remains to be evaluated.